OPTIMASI PERFORMA ANTARMUKA REACTIVE DENGAN MENERAPKAN SOCKET PROGRAMMING PADA SISTEM PEMBAYARAN SPP SMA DHARMAWANGSA - Fathur Rahman; Suendri (STORAGE: Jurnal Ilmiah Teknik dan Ilmu Komputer, 2026)
The development of information technology has encouraged the digitalization of administrative systems in education, including SPP payment management. However, at SMA Dharmawangsa, the recording process is still manual, so payment information is not directly accessible to students. This study aims to optimize the performance of the SPP payment system interface by implementing a Reactive User Interface and Socket Programming for payment information delivery. This research uses a descriptive qualitative approach with stages of problem identification, data collection, system design, implementation, and testing. The system is built as a web application using React.js on the client side and Nest.js on the server side. Socket Programming enables real-time communication between server and client, while the Reactive User Interface allows automatic interface updates without page reloads. The results show that the system delivers payment information faster and more responsively than the previous system. Information is updated directly after being recorded by the treasurer, improving delivery efficiency to students. Thus, Reactive User Interface and Socket Programming effectively optimize interface performance and support more efficient SPP management.